Caregivers’ evaluation of an educational material targeted to children with hydrocephalus - Caus, P. A. [UNESP]; Hamamoto Filho, P. T. [UNESP]; Avila, M. A.G. [UNESP] (Springer Nature, 2020)
Purpose: Modern pediatric neurosurgery succeeded in reducing ventricle-peritoneal shunt malfunctions and shunt revisions. However, some children may be submitted to many surgeries, posing burden to their caregivers. And most of caregiver assume responsibility for care without emotional preparation. It is up to health professionals to carry out the educational process. The aim of this study was to evaluate the knowledge, attitude, and practice of informal caregivers of children with hydrocephalus before and after intervention with previously developed educational material. Methods: This is a quasi-experimental, before-and-after study conducted with 32 informal caregivers of children with hydrocephalus. Data collection occurred in three stages: pre-test, educational intervention through educational material, and post-test. The knowledge, attitude, and practice survey was used as a pre-test and post-test assessment tool. Results: The mean score in the three domains (knowledge, attitude, and practice) was lower in the pre-test compared to the post-test. After caregivers read the educational material, the correct answer rate increased by 17% in the knowledge domain and 21.4% in the practice domain, with p values of < 0.01. In the attitude domain, there was a non-significant increase of 0.06 (2.0%, p = 0.161) points in the mean score between the pre-test and the post-test. Conclusion: The educational material enables the acquisition of knowledge of informal caregivers of children with hydrocephalus. This can be used by health professionals to strengthen the bond between professional care staff and family, and to facilitate the educational process.
Keywords: Caregivers; Hydrocephalus; Parent-child relations; Patient education